Health Seeking Behaviours Of Men Experiencing Infertility In The Accra Metropolis - Boadi (University of Ghana, 2020)
Health seeking behaviours are closely linked to a nation’s health status and its economic growth, and they are important as they define the disease outcomes and acceptance of health care. In Ghana, little is known about the health seeking behaviours of men experiencing infertility. The aim of this study was to explore the health seeking behaviours of men experiencing infertility in the Accra Metropolis. The theory of planned behaviour (TPB) was used as a guiding framework. An exploratory descriptive design was employed, and snowball and purposive sampling techniques were used to recruit 13 men diagnosed with and self-reported to have infertility. In-depth face-to-face interviews were conducted using a semi-structured interview guide. On average, each interview lasted between 45 and 60 minutes. The interviews were audio-recorded, transcribed verbatim, and analysed using thematic content analysis. Five major themes emerged based on the constructs of the TPB and three emerging themes were identified from the data. Participants described their health seeking behaviours in eight categories of behaviours. In addition, they also reported some barriers to their health seeking behaviours. Therefore, to improve the health seeking behaviours of men experiencing infertility, there is a need for health care providers to address the barriers identified by the participants. The findings of this study have implications for nursing practice, policy formulation, and infertility research.
MPhil. Nursing.
Keywords: policy formulation; infertility; verbatim; Ghana; nursing practice